Acquired resistance of pulmonary adenocarcinoma to initially successful targeted therapy due to EGFR mutation T790M - Jančaříková, Dana; Pešek, Miloš; Mináriková, Lucie; Topolčan, Ondřej; Holubec, Luboš; Minárik, Marek (Anticancer research, 2007)
According to previous reports in the literature, the T790M mutation indicates an acquired resistance to tyrosine kinase inhibitors. The initial positive effect of combination chemotherapy with erlotinib as the first line of treatment correlates with several positive predictors including the type of carcinoma, non-smoking status, occurrence of rash and the presence of exon 19 EGFR gene mutation. The case of a 32-year-old, non-smoker with non-contributory history patient, who was diagnosed with adenocarcinoma in the left lung T4N0M0 stage IIIB is reported. The patient underwent 6 cycles of chemotherapy with erlotinib, gemcitabine and cisplatin, followed by complete remission. Fifteen months after commencing therapy, disease recurred over subsequent therapy with erlotinib and then gefitinib. During that time, bone and cerebral metastases with pericardial effusion were detected. The patient died 7 months later. Genetic examination of tumour tissue collected at the beginning of therapy revealed activating exon 19 mutation in the EGFR gene. Later, during the relapse, the same mutation was still present and, in addition, a T790M mutation in exon 20 of EGFR was found. The subsequently acquired resistance against both erlotinib, as well as gefitinib was most likely a result of tumor cells acquiring the T790M mutations and escaping the drug effect. The authors recommend testing for T790M mutation presence in selected patients prior to targeted therapy with tyrosine kinase inhibitors.
Keywords: Molecular Sequence Data; financování organizované; Quinazolines; jednonukleotidový polymorfismus; lidé; Cisplatin; Deoxycytidine; cisplatina; mužské pohlaví; ErbB Receptors; nádory plic; mutace; adenokarcinom; Adult; chinazoliny; chemorezistence; Base Sequence; sekvence nukleotidů; Financing, Organized; Mutation; Humans; Drug Resistance, Neoplasm; deoxycytidin; Lung Neoplasms; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; molekulární sekvence - údaje; dospělí; Adenocarcinoma; erbB receptory; Male; Polymorphism, Single Nucleotide